Morphology‐Controlled Synthesis of a Novel Cu−Zn−S−O Nanocomposite for Pollutant Removal by Synergistic Effect of Adsorption and Photocatalysis. Issue 28 (26th July 2022) - Zhu, Wenli; Yang, Qiaoling; Du, Juan; She, Xiaohong; Yin, Pinpin
Abstract: The novel Cu−Zn−S−O nanocomposites have been successfully synthesized via a green microwave technique using preprepared ZnS and CuO nanoparticles. The Cu−Zn−S−O nanocomposites were highly sensitive to visible light. Meanwhile, Cu−Zn−S−O nanocomposites showed excellent adsorption capacity towards dye pollutants. Under the synergistic effect of adsorption and photocatalysis, various types of dye pollutants could be removed more quickly and efficiently by Cu−Zn−S−O (M=2) nanocomposite than pure CuO and ZnS nanoparticles. Furthermore, due to morphology‐controlled CuO, Cu−Zn−S−O nanocomposites were also different in the morphology and photoresponse, and even in the removal performance. The photodegradation mechanism investigation indicated that different types of dyes were mediated by different decisive reactive species. Additionally, Cu−Zn−S−O nanocomposites could be easily reused with higher activity. Abstract : Under the synergistic effect of adsorption and photocatalysis, the novel Cu−Zn−S−O nanocomposites obtained by the prepared CuO and ZnS showed excellent removal capacity to different types of dye pollutants. Moreover, in the photodegradation process, the typical acid, neutral and basic dyes were mediated by different decisive reactive species.